Lembaga Quasi Non Governmental Organization (Quango) Dalam Sistem Ketatanegaraan Indonesia: Majelis Ulama Indonesia - Abdilah, Ali; Novianto, Rico (Jurnal Hukum & Pembangunan, 2019)
Quasi Non-Governmental Organization institution or Quango is not as wellknown as other state institutions in Indonesia. However, it does not mean this institution does not exist in Indonesia. This article discusses the existence of Quango institution in Indonesian state institutions, especially Majelis Ulama Indonesia (MUI). This article explains the definition of Quango and the characteristics of Quango in several countries. Moreover, based on this article, it is believed that MUI can be classified as Quango in Indonesia state Institutions. To attain the expected result, this contribution employs normative legal studies by using some literature regarding Quango and its existence in some countries. Furthermore, this article also reviews some laws such as Law Concerning Halal Product Assurance, Law Concerning Sharia Bank, and some regulations and laws that have relation with the existence of MUI.